The Libyan Economy "Reality and Aspirations" A simple analytical study applied to the oil sector during the period from 1969 to 2014 - Al - Ghazwani, Nasser Abdul Karim (Arab Journal for Sciences and Research Publishing, 2016)
The objective of the research is to assess the performance of the Libyan economy in terms of the performance of the economic sectors, especially the oil sector, and to know its contribution positively or negatively to the progress and prosperity of the Libyan economy during the period (1969-2014). The descriptive research approach has been followed through the study of various economic sources and the most important results were: The Libyan economy is a developing economy characterized by duplication, ie, the existence of developed sectors, namely the oil and gas sectors and other backward sectors, and the consequent large structural imbalance within this economy. Weak absorptive capacity of foreign investments, mainly concentrated in the oil sector, weak private sector participation in these investments, the limited capacity of Libyan domestic products to compete internationally, and the inability of the state to create new investments.